Identification of European-wide clinical priorities for guideline development in the management of pre-invasive cervical disease. (August 2020) - Collins, Anna; L Moss, Esther; Nieminen, Pekka; Leeson, Simon; Redman, Charles WE
Highlights: EFC/ESGO aim to address practice variation in the management of CIN. Expert opinion to identify guideline topics was synthesised via a European Delphi. Selected topics will undergo systematic review to form European guidelines. Aiming to enable quality-assurance benchmarking and facilitate clinical audit. Abstract: Objective: Addressing management controversies in the treatment of pre-invasive cervical disease is a key priority for the European Federation for Colposcopy/European Society of Gynaecologic Oncology who aim to develop a practical handbook of European centred guidelines to address areas where there is a lack of high-quality evidence or identifiable practice variation. Clinical opinion across the EFC network was sought to identify topics likely to have the most impact on clinical practice for systematic review and development of practice recommendations. Study design: A scoping exercise comprising of a three-iteration modified Delphi with representation from each member society of the EFC was conducted in 2018. Round one identified 19 potential topics which were scored for importance using a five-point Likert scale by EFC members in round two and ranked. Results from round two were discussed at an open EFC satellite meeting resulting in exclusion of five topics. A third round of the 14 remaining topics was conducted to allow members to modify scores after viewing the second-round rankings. Responses were analysed and topics were allocated a weighted score. Results: Strategies for management of persistent HPV infection in the context of normal colposcopy and negative cytology was the highest overall weighted topic (4.40) followed by identification of appropriate length of follow up for ASCUS or LSIL prior to excisional treatment (3.95) and the impact of length of excision on patient outcomes (3.95). Topics to identify best practice for management of challenging topics scored highly including optimising follow up strategies for cervical stenosis (3.91) and management of HSIL in the under 25 year olds (3.64) or pregnancy (3.64). Conclusion: A European wide systematic modified-Delphi has prioritised six topics for systematic review and generation of clinical practice recommendations aiming to assist management in areas of controversy in pre-invasive cervical disease.